Global law and technology: reflections on the science of law and the model of jurist in the digital age - Julios-Campuzano, Alfonso de (Revista de Direitos e Garantias Fundamentais, 2023)
Ours is an era marked by globalisation, by the technological revolution and by the dizzying development of new information and communication technologies. In this digital and global era, the parameters that established the framework of human relations in a broad sense and the interpretative models of reality have been drastically altered. Thus, in the second modernity, we are witnessing the emergence of a new conception of law. The new legal paradigm of Global Law is outlined by three movements, displacements or translations of defining elements of the law of the first modernity and of the conception of the legal system on which it was based, which determine new characteristics that contribute to reconfiguring the conception of law and the legal system and propose a cosmopolitan reconsideration of the Science of Law and the role of the jurist in this change of era.